Superior sensory, motor, and cognitive performance in elderly individuals with multi-year dancing activities - Kattenstroth, Jan-Christoph; Kolankowska, Izabela; Kalisch, Tobias; Dinse, Hubert R. (Frontiers in Aging Neuroscience, 2010)
Aging is associated with a progressive decline of mental and physical abilities. Considering the current demographic changes in many civilizations there is an urgent need for measures permitting an independent lifestyle into old age. The critical role of physical exercise in mediating and maintaining physical and mental fitness is well-acknowledged. Dance, in addition to physical activity, combines emotions, social interaction, sensory stimulation, motor coordination and music, thereby creating enriched environmental conditions for human individuals. Here we demonstrate the impact of multi-year (average 16.5 years) amateur dancing (AD) in a group of elderly subjects (aged 65 to 84 years) as compared to education-, gender- and aged-matched controls (CG) having no record of dancing or sporting activities. Besides posture and balance parameters, we tested reaction times, motor behavior, tactile and cognitive performance. In each of the different domains investigated, the AD group had a superior performance as compared to the non-dancer CG group. Analysis of individual performance revealed that the best participants of the AD group were not better than individuals of the CG group. Instead, the AD group lacked individuals showing poor performance, which was frequently observed for the CG group. This observation implies that maintaining a regular schedule of dancing into old age can preserve cognitive, motor and perceptual abilities and prevent them from degradation. We conclude that the far-reaching beneficial effects found in the AD group make dance, beyond its ability to facilitate balance and posture, a prime candidate for the preservation of everyday life competence of elderly individuals.